The CALLY Index as a Predictive Tool for Postoperative Pneumonia in Esophageal Squamous Cell Carcinoma: A Retrospective Cohort Study - Xu Z; Chen C; Zhao J; Li C; Zang B; Xiong X (Journal of Inflammation Research)
Zhiyun Xu,* Chen Chen,* Jianqiang Zhao, Chenglin Li, Bao Zang, Xinkui Xiong Department of Thoracic Surgery, The Affiliated Huaian No. 1 People’s Hospital of Nanjing Medical University, Huai’an, 223300, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xinkui Xiong, Email xiongxk714@163.com Bao Zang, Email zangbaofqin@sina.comBackground: Esophageal Squamous Cell Carcinoma poses a significant global health challenge, with postoperative pneumonia being a critical complication affecting recovery and prognosis. Traditional predictive models have proven to be insufficient. This study investigates the CALLY Index as a novel tool for predicting postoperative pneumonia in resectable ESCC patients.Methods: A retrospective cohort study was conducted involving 209 patients undergoing thoraco-laparoscopic McKeown procedure for resectable ESCC from January 2019 to December 2022. Patients with chronic pulmonary diseases or previous malignancies were excluded. Clinical data, including age, gender, tumor stage, preoperative albumin, lymphocyte counts, and CRP levels, were analyzed to calculate the CALLY Index. Univariate and multivariate logistic regression analyses were performed to identify independent predictors of postoperative pneumonia, and receiver operating characteristic curves were used to evaluate the CALLY Index’s predictive validity.Results: Among the cohort, 63.8% of patients with low CALLY Index scores developed postoperative pneumonia compared to 12.1% with high scores (p < 0.001). The optimal cutoff for the CALLY Index was determined to be 3.47, achieved sensitivity of 0.721 and specificity of 0.865. In multivariate analyses, the CALLY Index remained a strong predictor of pneumonia (adj. OR: 0.64, 95% CI: 0.51– 0.77, p < 0.001). Notably, higher tumor stage and prolonged hospital stays were also associated with an increased risk of pneumonia.Conclusion: The CALLY Index is an effective predictor of postoperative pneumonia in patients with esophageal squamous cell carcinoma, especially when evaluated in conjunction with tumor stage and length of hospital stay. This approach can aid clinicians in conducting early risk assessments and customizing therapeutic strategies, ultimately enhancing patient management and outcomes.Keywords: esophageal squamous cell carcinoma, postoperative pneumonia, CALLY Index, predictive tool, surgical outcomes